2017
DOI: 10.1186/s40623-017-0658-7
|View full text |Cite
|
Sign up to set email alerts
|

Spectral moments for the analysis of frequency shift, broadening, and wavevector anisotropy in a turbulent flow

Abstract: Turbulence represents essentially random fluctuations that evolve both spatially and temporally, and appear in various geophysical and space science applications. A spectral moment method is proposed to characterize the turbulence energy spectra in the wavevector and frequency domain in the lowest-order sense. The frequency shift velocity and the random sweeping velocity are obtained from the first-order and second-order moments of the wavenumber-frequency spectra. The maximum extension direction and the ellip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The energy moment method is used to calculate the signal frequency [34] in this study. The energy moment balance method is shown in figure 2.…”
Section: Frequency Of Driving Signalmentioning
confidence: 99%
“…The energy moment method is used to calculate the signal frequency [34] in this study. The energy moment balance method is shown in figure 2.…”
Section: Frequency Of Driving Signalmentioning
confidence: 99%
“…In the k-w domain, Taylor's hypothesis corresponds to a straight line, which contrasts with the continuous distributions observed in nature, as the energy density function (EDF) spreads in the vicinity of this linear prediction. The concept of spreading leads to the random sweeping hypothesis, which was exploited earlier in [47], and later, e.g., in [40,48,49]. A state-of-the-art review of these k-w spectrum models is presented in [49].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of spreading leads to the random sweeping hypothesis, which was exploited earlier in [47], and later, e.g., in [40,48,49]. A state-of-the-art review of these k-w spectrum models is presented in [49].…”
Section: Introductionmentioning
confidence: 99%
“…Boldyrev in [ 25 ] also concluded that MHD turbulence is not completely described by either the or scales; the scales depend on the strength of the external magnetic field: scale applies when the mean magnetic field is strong while scale applies when the external magnetic field is weak. We refer to the review by Verma [ 19 ] for the several phenomenological theories on MHD turbulence, the book by Davidson et al [ 2 ] for the biographies and works of some of the prominent contributors to the area, and [ 26 , 27 , 28 , 29 ] and the references in there for interesting applications and recent developments.…”
Section: Introductionmentioning
confidence: 99%